Investing in development : a practical plan to achieve the Millennium Development Goals : report to the UN Secretary-General (Earthscan LondonGB, 2005)
Examines the importance of the Millennium Development Goals. Assesses the progress made to date and looks at the shortfall. Highlights country-level processes to achieve the goals. Makes recommendations for the international system to support country-level processes. Notes the costs and benefits of achieving the Millennium Development Goals.
Keywords: POVERTY ALLEVIATION